1980
DOI: 10.1128/jb.144.3.1043-1047.1980
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-sensitive glutamate dehydrogenase mutants of Salmonella typhimurium

Abstract: Mutants of Salmonella typhimurium defective in glutamate dehydrogenase activity were isolated in parent strains lacking glutamate synthase activity by localized mutagenesis or by a general mutagenesis combined with a cycloserine enrichment for glutamate auxotrophs. Two mutants with temperature-sensitive phenotypes had glutamate dehydrogenase activities that were more thermolabile than that of an isogenic control strain. Eight other mutants had less than 10% of the wild-type glutamate dehydrogenase activity. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Glutamate dehydrogenases catalyze the oxidative amination ofa-ketoglutarate to glutamate and the reductive deamination of glutamate. This enzyme, therefore, can function in either ammonia assimilation or glutamate catabolism (14,6,7,11,12,14,15,17,18). Although glutamate dehydrogenase has been found in many species of Bacillus (1,10,18), there have been conflicting reports on the presence of a glutamate dehydrogenase in Bacillus subtilis (1,9,12,14,17,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Glutamate dehydrogenases catalyze the oxidative amination ofa-ketoglutarate to glutamate and the reductive deamination of glutamate. This enzyme, therefore, can function in either ammonia assimilation or glutamate catabolism (14,6,7,11,12,14,15,17,18). Although glutamate dehydrogenase has been found in many species of Bacillus (1,10,18), there have been conflicting reports on the presence of a glutamate dehydrogenase in Bacillus subtilis (1,9,12,14,17,18).…”
mentioning
confidence: 99%
“…Cell growth was monitored by measuring the turbidity at 600 nm, and the cultures were harvested at an absorbance of between 0.6 and 0.8. The cell pellets were suspended in either 40 mM potassium phosphate buffer, pH 7.5, containing 1 mM EDTA, 12 mM ,f-mercaptoethanol, 12 mM glutamine, 5 mM histidine, 1 mM NaN3, 1 mM phenylmethylsulfonyl fluoride, and 30% glycerol (buffer A); or 50 mM potassium phosphate buffer, pH 6.5, containing 1 mM EDTA, 6 dehydrogenase. Crude extracts, prepared in either buffer A or B as previously described (8), contained identical activities for glutamate dehydrogenase.…”
mentioning
confidence: 99%
“…It was show (Fig. 4) that the insert DNA in pJB109 is homologous to the region on the pncA side of gdhA52, a mutation that causes the production of a temperature-sensitive GDH (14,30 the EcoRIIPvuII fragment must be located in the gdhA structural gene. Since it had been shown that the direction of gdhA transcription is from the nit side of the gene toward pncA on the S. typhimurium chromosome (30; S. A. Rosenfeld, Ph.D. thesis), the EcoRIIHindIII fragment of pJB105 was inferred to contain the gdhA promoter.…”
Section: Discussionmentioning
confidence: 99%
“…The question of why S. typhimurium cells growing with either excess or limiting ammonia have high GDH activities, even when it is not required to synthesize glutamate, is of particular interest (5,14,15,30). The analysis of several strains with mutations in the structural gene for GDH, gdhA, has demonstrated that the enzyme activity is not essential as long as glutamate synthase is functional (14,15,30).…”
mentioning
confidence: 99%
See 1 more Smart Citation